2019
DOI: 10.1136/gpsych-2019-100156
|View full text |Cite
|
Sign up to set email alerts
|

Very early family-based intervention for anxiety: two case studies with toddlers

Abstract: Anxiety disorders represent the most common category of psychiatric disorder in children and adolescents and contribute to distress, impairment and dysfunction. Anxiety disorders or their temperamental precursors are often evident in early childhood, and anxiety can impair functioning, even during preschool age and in toddlerhood. A growing number of investigators have shown that anxiety in preschoolers can be treated efficaciously using cognitive–behavioural therapy (CBT) administered either by training the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Here it is potentially important to include parents in treatment. Some research has shown that parents can assist their children recover from anxiety in general (Hirshfeld-Becker et al, 2019), although we are not aware of any family-based interventions for mathematics anxiety.…”
Section: A Novel Individualized Cognitive Behavioral Therapy (I-cbt) For Mathematics Anxietymentioning
confidence: 98%
“…Here it is potentially important to include parents in treatment. Some research has shown that parents can assist their children recover from anxiety in general (Hirshfeld-Becker et al, 2019), although we are not aware of any family-based interventions for mathematics anxiety.…”
Section: A Novel Individualized Cognitive Behavioral Therapy (I-cbt) For Mathematics Anxietymentioning
confidence: 98%
“…Hirshfield Becker et al [56] showed that anxiety in pre-schoolers aged below 4 years can also be treated using a modified form of CBT which obviously involved training the parents to be the co-therapists. The program involved teaching parents how to monitor anxious responses, restructure their own thoughts, identify what responses are unhelpful to their child's anxiety, model adaptive coping, engage in nondirective play with the child, use praise to reinforce better coping responses and also plan and implement graded exposure exercises.…”
Section: Suggested Modifications For the Preschool Childmentioning
confidence: 99%
“…In another article, Hirshfeld-Becker and colleagues report on two case studies that tested the feasibility and potential efficacy of family-based cognitive-behavioral therapy (CBT) for anxiety in toddlers 11. The authors note that anxiety in young children tends to be persistent and interferes with cognitive and social development.…”
mentioning
confidence: 99%